Individual-based Creatine Kinase Reference Values in Response to Soccer Match-play - Ribeiro, João; Gantois, Petrus; Moreira, Vitor; Miranda, Francisco; Romano, Nuno; Nakamura, Fábio Yuzo (International Journal of Sports Medicine, 2022)
The aim of the present study was to determine the creatine kinase reference limits for professional soccer players based on their own normal post-match response. The creatine kinase concentration was analyzed in response to official matches in 25 players throughout a 3-year period. Samples were obtained between 36–43 hours following 70 professional soccer matches and corresponded to 19.1±12.1 [range: 6–49] samples per player. Absolute reference limits were calculated as 2.5th and 97.5th percentile of the samples collected. Creatine kinase values were also represented as a percentage change from the individual’s season mean and represented by 90th, 95th and 97.5th percentiles. The absolute reference limits for creatine kinase concentration calculated as 97.5th and 2.5th percentiles were 1480 U.L−1 and 115.8 U.L−1, respectively. The percentage change from the individual’s season mean was 97.45±35.92% and players were in the 90th, 95th and 97.5th percentiles when the percentages of these differences were 50.01, 66.7, and 71.34% higher than player’s season mean response, respectively. The data allowed us to determine whether the creatine kinase response is typical or if it is indicative of a higher than normal creatine kinase elevation and could be used as a practical guide for detection of muscle overload, following professional soccer match-play.
Keywords: CK; monitoring; muscle damage